Tonic glutamate in CA1 of aging rats correlates with phasic glutamate dysregulation during seizure. Issue 11 (29th September 2014) - Stephens, Michelle L.; Williamson, Anne; Deel, Megan E.; Bensalem‐Owen, Meriem; Davis, Verda A.; Slevin, John; Pomerleau, Francois; Huettl, Peter; Gerhardt, Greg A.
Summary Objective Characterize glutamate neurotransmission in the hippocampus of awake‐behaving rodents during focal seizures in a model of aging. Methods We used enzyme‐based ceramic microelectrode array technology to measure in vivo extracellular tonic glutamate levels and real‐time phasic glutamate release and clearance events in the hippocampus of awake Fischer 344 rats. Local application of 4‐aminopyridine (4‐AP) into the CA1 region was used to induce focal motor seizures in different animal age groups representing young, late‐middle aged and elderly humans. Results Rats with the highest preseizure tonic glutamate levels (all in late‐middle aged or elderly groups) experienced the most persistent 4‐AP‐induced focal seizure motor activity (wet dog shakes) and greatest degree of acute seizure‐associated disruption of glutamate neurotransmission measured as rapid transient changes in extracellular glutamate levels. Significance Increased seizure susceptibility was demonstrated in the rats with the highest baseline hippocampal extracellular glutamate levels, all of which were late‐middle aged or aged animals. The manifestation of seizures behaviorally was associated with dynamic changes in glutamate neurotransmission. To our knowledge, this is the first report of a relationship between seizure susceptibility and alterations in both baseline tonic and phasic glutamate neurotransmission.